Tiktok Media Overload Emotional Balance in Digitalization - Syifa Nurul Maola; Nadia Aulia Nadhirah; Syamsu Yusuf LN (Journal of Education and Counseling (JECO), 2023)
The TikTok application is an application that is widely downloaded by the public. The problem in this article concerns the excessive use of TikTok media which continuously causes emotional imbalance and affects individual mental health. Emotional imbalance due to the influence of TikTok media is a problem that often occurs among teenagers and even adults. The purpose of this article is to find out how emotional balance in digitalization affects individual mental health. The research method used by the author is literature study which consists of data collection, selection and clarification of data sources, data analysis and compiling reports. The results obtained from the literature study show that digitalization has made social media a daily need for individuals. This need can cause addiction to the user. Excessive use of TikTok media causes anxiety due to social communication, negative content, and negative comments causing the individual's emotional balance to be disturbed due to changes in mood. Emotional balance that is not optimal affects mental health and can result in stress, depression and high anxiety disorders. Excessive use will also result in addiction and have a negative impact on emotional balance, mental and physical health. Every individual needs to maintain and supervise the use of social media, especially TikTok . Individuals can use time management and limit their use of TikTok media to maintain emotional balance.